Correlation of serum acute-phase proteins with bone repair in rabbits (Oryctolagus cuniculus) submitted to partial radio ostectomy - Calciolari, Karina [UNESP] (2021)
Bone trauma triggers an acute inflammatory response, which can alter the serum concentration of acute-phase proteins (PFA). We aimed to evaluate the effectiveness of PFA measurement as a laboratory biomarker for inflammation related to bone regeneration. A partial ostectomy of the right radius was performed on 22 young male rabbits. The complete blood count, albumin, ceruloplasmin, haptoglobin, C-reactive protein, and transferrin levels were recorded and correlated with the radiographic evolution of bone healing. Statistically the best correlations with the inflammatory process and radiological findings were reported with haptoglobin and transferrin compared to the other measured PFAs. Haptoglobin and transferrin showed a maximum peak 24 and 36 hours after surgery, respectively. Transferrin displayed signs of decrease in the first 6 hours after surgery, in advance of the leukocyte response. The measurement of acute-phase proteins proved to be viable, considering the conditions in which the present study was carried out. Among all variables studied, haptoglobin and transferrin showed best correlation with the inflammatory process of bone healing. Additional studies are needed to determine the sensitivity of acute-phase proteins as predictors of complications in the treatment of fractures.